Learning to Teach in Urban Schools : the Transition from Preparation to Practice. - Hollins, Etta R. (Taylor & Francis, 2011)
This book is about the transition from teacher preparation to teaching practice in urban school settings. It provides a clear presentation of the challenges, resources, and opportunities for learning to teach in urban schools; examples of the experiences, perceptions, and practices of teachers who are effective in urban schools and those who are not; a detailed account of the journey of a team of teachers who transformed their practice to improve learning in a low performing urban school; an approach that can be used by novice teachers in joining a teacher community and making the transition f.